ART AND SOCIETY RELATIONSHIP: कला और समाज का अर्न्तसम्बन्ध - Sonia, Ashutosh Kumar (International Journal of Research -GRANTHAALAYAH, 2019)
English : The painting is produced for the purpose of society. Arts have always been responsible for social facts and they express the wishes of society. The sense of painting (art) is hidden in the arts. It is free from rules even after being bound in social bond. Art is a part of the culture of the society, which the society keeps on progressing as tradition and art always lives. The artist creates a relationship only with the appearance, activities and feelings of society in the external world. In his creation, social emotions are directly related to human instincts. The expression of these feelings is expressed in artistic creation, as a result the form of art is also universal. The talent of the artist, his self-power and his artistic elements, in the form of art, harmonize with the nature and emotions of the society, giving it a wider look. Most of the subjects of art are the problems of the society then, in this purpose, the personality takes a secondary form in creation and the reflection of the needs of the society is reflected in its creation. In such a situation, the artist wants to achieve self-peace through expressive purpose. In this situation one chooses his own path to achieve the objective, but can never remain separate from society. But in front of technical principles, the goal of the viewer’s joy and self-power remains. On the basis of the principle, the form of art created in the first position is pure and original and in the second position, the form of art is practical and originality away from it for the goal. As a result, many techniques have to be adopted and presented as crafts. Hindi : चित्रकला समाज के उद्‌देश्य पूर्ति के लिए निर्मित की जाती है। कलाएँ सामाजिक तथ्यों के प्रति सदैव उत्तरदायी रही हैं तथा इनमें समाज की इच्छाओं की अभिव्यक्ति होती है। कलाओं में चित्रकला (कला) का भाव छिपा रहता है। यह सामाजिक बन्धन में बंधे होने के पश्चात्‌ भी नियमों से स्वतन्त्र होती है। समाज की संस्कृति का एक अंग कला है, जिसको समाज परम्परा के रूप में क्रमशः आगे बढ़ाता रहता है और कला सदैव जीवित रहती है। कलाकार वाह्‌य जगत के रूप-स्वरूप, गतिविधियों एवं समाज की भावनाओं से सम्बन्ध बनाकर ही सृजन किया करता है वह अपने सृजन में सामाजिक भावनाओं का मानव-वृत्तियों से सीधा सम्बन्ध रखता है। कलात्मक सृजन में इन्ही भावनाओं की अभिव्यक्ति होती है, परिणाम स्वरूप कला का रूप भी विश्वव्यापी होता है। कलाकार की प्रतिभा, उसकी आत्मशक्ति एवं उसके कलात्मक तत्व, कला के रूप में समाज के स्वरूप और भावनाओं के साथ सामंजस्य जोड़कर, उसको व्यापक रूप प्रदान करते हैं। कला के अधिकांश विषय तत्कालीन समाज की समस्यायें ही होती है, इस उद्‌देश्य से किये गये सृजन में व्यक्तित्व गौण रूप ले लेता है ओर समाज की आवश्यकताओं का प्रतिबिम्ब उसके सृजन मे स्पष्ट झलकता रहता है। कलाकार ऐसी स्थिति में उद्‌देश्य अभिव्यक्ति के माध्यम से आत्मशान्ति प्राप्त करना चाहता है। इस स्थिति में उद्‌देश्य के प्राप्ति के लिए स्वयं अपना मार्ग चुनता है, लेकिन समाज से कभी अलग नहीं रह सकता है। किन्तु तकनीकी सिद्धान्तों के समक्ष दर्शक के आनन्द और आत्मशक्ति का लक्ष्य रहता है। सिद्धान्त के आधार पर पहली स्थिति में सृजित कला का रूप शुद्ध और मौलिक होता है तथा दूसरी स्थिति में लक्ष्यपूर्ति के लिए कला का रूप व्यावहारिक एवं मौलिकता उससे दूर हो जाती है। फलस्वरूप अनेकानेक तकनीकों को ग्रहण करना तथा उन्हें शिल्प के रूप में प्रस्तुत करना होता है।